Differences in the effect of repetitive transcranial magnetic stimulation and median nerve electrical stimulation in patients with prolonged disorders of consciousness after intracerebral hemorrhage: a randomized controlled trial protocol - Guoshun Zhao; Mingzhu Fang; Shiyu Han; Xiaoke Peng; Anqin Dong (Frontiers in Neurology)
BackgroundRepetitive transcranial magnetic stimulation (rTMS) and median nerve electrical stimulation (MNES) are two non-invasive neuromodulation techniques that have demonstrated potential in facilitating the recovery of consciousness in patients with impaired consciousness. However, existing studies on awakening interventions for patients with prolonged disorders of consciousness (pDoC) following intracerebral hemorrhage remains limited. In particular, systematic comparisons of the efficacy of rTMS versus MNES in this specific patient population are lacking.MethodsThis is a single-center randomized controlled trial in which 45 patients will be randomly assigned to the control group, rTMS group and MNES group. The intervention period will lasts 4 weeks. All patients underwent multimodal assessments before and at the end of treatment, which were used to comprehensively evaluate their recovery of consciousness and changes in brain function. The assessments includes the Coma Recovery Scale, electroencephalogram, event-related potentials (P300 and mismatched negative) and functional near-infrared spectroscopy.DiscussionThis study represents the first systematic comparison of the efficacy between rTMS and MNES in patients with pDoC following intracerebral hemorrhage. The objective is to employ multimodal assessment techniques to provide clinical references into the individualized application of these neuromodulation therapies.Clinical trial registrationhttps://www.chictr.org.cn/, identifier ChiCTR2400082022.